THE INFLUENCE OF CAREER DEVELOPMENT AND TRAINING ON JOB SATISFACTION IN KARAWANG DISTRICT EMPLOYEES - Wahyu Indri Hasanah; Wike Pertiwi; Budi Rismayadi (PT. Berkah Digital Teknologi, 2024)
Purpose: To analyze the influence of career development and training on employee job satisfaction at the BKPSDM Karawang office. Research Methodology: This study employed a quantitative verification method. The population consisted of 53 employees, with all employees included using saturated sampling. Data analysis was conducted using multiple linear regression through SPSS v.25 software. Results: Career development showed a positive influence on job satisfaction. Training demonstrated a positive and significant influence on employee job satisfaction at BKPSDM Karawang. The study found that both Career Development (X1) and Training (X2) variables have an influence on employee Job Satisfaction (Y). Limitations: The study was confined to the BKPSDM Karawang office and focused solely on career development and training as factors affecting job satisfaction. Other potential influential variables such as discipline, workload, work schedule, motivation, environment, and leadership style were not examined in this research. Contribution: This research provides insights into the relationships between career development, training, and job satisfaction in a local government office setting. The findings can inform management strategies to enhance employee job satisfaction by focusing on career development and training programs in similar public sector environments.